2021
DOI: 10.1155/2021/6699033
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Study of Safrole and Methyl Eugenol after Oral Administration of the Essential Oil Extracts of Asarum in Rats by GC-MS

Abstract: Asarum is a traditional medicine and has been widely used as remedies for inflammatory diseases, toothache, headache, local anesthesia, and aphthous stomatitis in China, Japan, and Korea. Our previous research found that safrole and methyl eugenol were vital compounds that contribute to distinguish the different species and raw Asarum and its processed products apart. The pharmacokinetics of safrole and methyl eugenol after oral administration of Asarum extract has not been reported yet. In this study, a rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Essential oils composition has also been reported to be influenced with the light quality in different aromatic plant species, e.g., rosemary [33], Japanese mint [34], thyme, marjoram and oregano [9]. In Asarum essential oils, methyleugenol and eucarvone are the active ingredients [35,36], whereas safrole and myristicin are the toxic ingredients [37,38]. The results, that elemicin, 3,5-dimethoxytoluene and methyleugenol were accumulated in higher quantities in response to light quality V, can be a useful observation.…”
Section: Discussionmentioning
confidence: 99%
“…Essential oils composition has also been reported to be influenced with the light quality in different aromatic plant species, e.g., rosemary [33], Japanese mint [34], thyme, marjoram and oregano [9]. In Asarum essential oils, methyleugenol and eucarvone are the active ingredients [35,36], whereas safrole and myristicin are the toxic ingredients [37,38]. The results, that elemicin, 3,5-dimethoxytoluene and methyleugenol were accumulated in higher quantities in response to light quality V, can be a useful observation.…”
Section: Discussionmentioning
confidence: 99%
“…Network pharmacological analysis of AEO components showed that methyl eugenol and safrole could act on the inflammatory genes COX-1 and LAT4H ( Liu and Wang, 2022 ). The aforementioned data suggested that methyl eugenol and safrole are the active components of AEO and are may responsible for their anti-inflammatory effects ( Fan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%